2015
DOI: 10.1260/1369-4332.18.10.1597
|View full text |Cite
|
Sign up to set email alerts
|

Imperfect Correlation of Vortex-Induced Fluctuating Pressures and Vertical Forces on a Typical Flat Closed Box Deck

Abstract: A wind tunnel test of synchronized pressure measurement on a spring-suspended sectional model of a flat closed box deck at a large scale of 1/20 was carried out by taking Xiangshan Harbour Bridge in China as background. The chordwise correlation of the fluctuating aerodynamic pressures (FAP) on the surface of the box deck was then investigated at both stationary state and vortex-induced resonance (VIR) states of the deck model. Afterwards, an approximate approach was developed for estimating the spanwise corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Furthermore, the test results also indicate that the span-wise correlation of the total VIF during VIV will increase as the section configuration evolves from blunt body to streamline body. The phenomena that structural motion may enhance the span-wise correlation of VIF on a similar flat STR girder of about 9.1:1 width-to-depth ratio, a centrally-slotted box girder and a 5:1 width-to-depth ratio REC girder has also been reported by Meng et al (2015), Zhu et al (2017) and Zhang et al (2022), respectively.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Furthermore, the test results also indicate that the span-wise correlation of the total VIF during VIV will increase as the section configuration evolves from blunt body to streamline body. The phenomena that structural motion may enhance the span-wise correlation of VIF on a similar flat STR girder of about 9.1:1 width-to-depth ratio, a centrally-slotted box girder and a 5:1 width-to-depth ratio REC girder has also been reported by Meng et al (2015), Zhu et al (2017) and Zhang et al (2022), respectively.…”
Section: Introductionmentioning
confidence: 81%
“…As discussed in Meng et al (2015), the span-wise correlation coefficient of the PVSF ρ VS on the flat box deck, ρ VS , can be expressed by the following equation ( 11):…”
Section: Span-wise Correlation Coefficient Of Pvsfmentioning
confidence: 99%
See 2 more Smart Citations
“…Ehsan et al [10] found that the freedom in which the structure oscillated would affect the spanwise correlation of the aerodynamic forces of the main girder with an H section shape and a side ratio of 4. Meng et al [19] investigated the imperfect correlation of vortex-induced fluctuating pressure and the integrated vertical fluctuating force on the flat closed box deck using a large-scale section model and found that it can be greatly enhanced or changed by the deck vibration for most parts of the deck. Xu et al [20] studied the characteristics of torsional VIV and the correlation between the surface pressure and VIF for a streamlined box girder using a small-scale section model.…”
Section: Introductionmentioning
confidence: 99%